2021
DOI: 10.7554/elife.63538
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin promotes AApoAII amyloidosis and peroxisome proliferation in mice by activating the PPARα signaling pathway

Abstract: Curcumin is a polyphenol compound that exhibits multiple physiological activities. To elucidate the mechanisms by which curcumin affects systemic amyloidosis, we investigated amyloid deposition and molecular changes in a mouse model of amyloid apolipoprotein A-II (AApoAII) amyloidosis, in which mice were fed a curcumin-supplemented diet. Curcumin supplementation for 12 weeks significantly increased AApoAII amyloid deposition relative to controls, especially in the liver and spleen. Liver weights and plasma Apo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…This showed that the PPAR pathway is a potential target for hydrogen. The Apoa-II mRNA expression was increased through the activation of PPAR-α [39]. Therefore, Apoa2, as a link in the PPAR pathway, also has the potential to be a target of hydrogen.…”
Section: Discussionmentioning
confidence: 99%
“…This showed that the PPAR pathway is a potential target for hydrogen. The Apoa-II mRNA expression was increased through the activation of PPAR-α [39]. Therefore, Apoa2, as a link in the PPAR pathway, also has the potential to be a target of hydrogen.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that oxidative stress inhibitors (such as tempol and apocynin) reduced apoA-II amyloid deposition [132]. Contrary to expectations, via activation of the PPARα pathway, curcumin increased apoA-II amyloid deposition in mice that were induced to develop systemic amyloidosis [135].…”
Section: Role Of Apoa-ii In Amyloidosismentioning
confidence: 97%